Shifts in Paediatric Road Trauma Dynamics Pre- vs. Post-COVID-19 Lockdown: Insights from a Major Trauma Centre - Rayan Jafnan Alharbi; Hussin Albargi; Ateeq Almuwallad; Naif Harthi; Sharfuddin Chowdhury (Springer, 2024)
Abstract Background The COVID-19 pandemic has brought unprecedented changes globally, significantly affecting public health sectors, including paediatric road trauma. This study aims to explore the changes in paediatric road trauma presentations and outcomes before and after the COVID-19 lockdown. Methods This retrospective study analysed paediatric trauma data from the Saudi TraumA Registry (STAR) from August 2017 to December 2022, comparing pre- and post-COVID-19 lockdown periods (August 2017-March 2020 and July 2020-December 2022, respectively). The study analysed demographic data, mechanism of injury, severity, ICU admissions, and mortality rates using multivariate logistic regression models. Results Out of 950 paediatric trauma cases analysed, there was an 44.2 [561/389 = 1.442] % increase in the number of cases post-lockdown. A significant shift was noted in the age group of 5-9 years, with cases increasing from post-lockdown. Head injuries were the most prevalent type of injury, with their proportion slightly increasing from 163 (20.5%) pre-lockdown to 248 (23.2%) post-lockdown. The ICU admission were consistent across both periods, while the definitive care mode of arrival post-lockdown showed a notable shift towards private or government ambulances. Conclusion Our study provides critical insights into the significant impact of the COVID-19 on paediatric road trauma. The observed increase in trauma cases post-pandemic, particularly among younger children and a notable rise in driver-related injuries among adolescents, underscores the profound effect of lockdown measures and subsequent societal changes on paediatric health. Efforts to reduce paediatric traffic injuries require collaboration among parents, educators, healthcare professionals, policymakers, and the community at large.